Predictors of Asthma Treatment Adherence in Rural Appalachian Adults with Asthma - Heidi Putman (Rural Nurse Organization; Binghamton University, 2004)
This descriptive, non-experimental study in a sample of 102 rural Appalachian adults with asthma evaluated relationships between treatment regimen adherence and health beliefs, attitude, behavioral intention, and age. Major predictors of adherence were health beliefs and attitude toward asthma. Findings provide partial support for the theorized relationships. Recommendations include future intervention studies designed to improve asthma care outcomes among rural Appalachian adults diagnosed with asthma.